Isolation and synthesis of anthraquinones and related compounds of Rubia cordifolia - RAM SINGH; GEETANJALI (Journal of the Serbian Chemical Society, 2005)
Anthraquinones and their glycosides, along with other compounds, have been isolated and characterized from the acetone:water (1:1) percolation of dried roots of Rubia cordifolia. Selected anthraquinones were synthesized using montmorillonite clays under solventless condition in 75 to 85 % yield.